MAINTENANCE OF PERIPHERALLY INSERTED CENTRAL CATHETER (PICC) PATENCY: AN EXPERIENCE REPORT IN A UNIVERSITY HOSPITAL IN BELÉM, PARÁ (Editora Impacto Científico, 2025)
This experience report aims to describe the practices carried out during a supervised internship at a university hospital in Belém do Pará, from May to September 2025, focusing on the maintenance of the Peripherally Inserted Central Catheter (PICC) patency. The central issue lies in the risks associated with catheter obstruction and mechanical complications resulting from inadequate use of this device, which is essential for prolonged intravenous therapies. The intervention was guided by the flushing technique as a preventive measure against obstructions, aligned with evidence-based protocols and continuous monitoring of the device’s condition. Methodologically, this study adopts a qualitative design, configured as a descriptive account of hospital-based practical experiences supported by updated scientific evidence. The results highlighted that the systematic use of saline flushing, combined with strict adherence to aseptic techniques and proper documentation of interventions, significantly reduced complications, ensuring patient safety and optimizing therapeutic outcomes. It is concluded that the implementation of standardized care protocols grounded in scientific evidence is crucial to preventing mechanical complications in PICC use, thereby enhancing the effectiveness of intravenous therapy and reinforcing professional performance in hospital practice.DOI: https://doi.org/10.56238/edimpacto2025.091-001